2017
DOI: 10.1111/jopr.12631
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immediate Implants Augmented with Autogenous Bone/Melatonin Composite Graft in the Esthetic Zone: A Randomized Controlled Trial

Abstract: Within the limitations of this study, immediate implants augmented with ABG/melatonin composite graft would be a valuable option in the esthetic zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Melatonin was utilized in this investigation because it has been shown to reduce the generation of free radicals in osteoclasts, a kind of bone cell. Osteoclastogenesis [ 24 ] produces a free radical, which is detoxified by the antioxidant properties of vitamin E. The overall mean marginal bone loss from baseline to nine months in group A is 1.5±0.33 and in group B is 1.37±0.56, which is in accordance with the study conducted by El-Gammal et al [ 25 ] and Hazzaa et al [ 26 ]. Our results show that there is a reduction of crestal bone loss in group B (melatonin placed implants) than in group A (implants without melatonin).…”
Section: Discussionsupporting
confidence: 87%
“…Melatonin was utilized in this investigation because it has been shown to reduce the generation of free radicals in osteoclasts, a kind of bone cell. Osteoclastogenesis [ 24 ] produces a free radical, which is detoxified by the antioxidant properties of vitamin E. The overall mean marginal bone loss from baseline to nine months in group A is 1.5±0.33 and in group B is 1.37±0.56, which is in accordance with the study conducted by El-Gammal et al [ 25 ] and Hazzaa et al [ 26 ]. Our results show that there is a reduction of crestal bone loss in group B (melatonin placed implants) than in group A (implants without melatonin).…”
Section: Discussionsupporting
confidence: 87%
“…It was reported that in a one-year randomized controlled trial (RCT), melatonin improved bone mineral density, increased serum bone formation markers, and decreased the fracture risk probability compared with the control group [ 104 ]. Another RCT showed that autogenous bone/melatonin composite graft improves bone density and reduced marginal bone loss in the esthetic zone [ 105 ].…”
Section: Advances In Antiosteoporosis Drugs and Biomaterialsmentioning
confidence: 99%
“…Seet et al (2015) was considered unclear for incomplete outcome data and high risk for selective reporting. Other bias was considered the administration of other substances (Chitsazi et al, 2017; Cobo‐Vázquez et al, 2014; Seet et al, 2015; Isik et al, 2008; Ansari et al, 2018; Faghihian et al, 2018; Torun & Yüceer, 2019; Elsabagh et al, 2020; Lozano et al, 2021; El‐Gammal et al, 2016; Hazzaa et al, 2019; Lee & Curtin, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the cellular effects of melatonin, this substance has been used in the medical‐dental area as an adjunctive anti‐inflammatory with the purpose of reducing the inflammation and accelerating the repair after dental procedures (Cutando et al, 2015; Hazzaa et al, 2019). Thus, the purpose of the study was to investigate different outcomes that melatonin can promote on dental conditions or dental procedures, having as a question to be answered “Does the melatonin administered systemically or topically ameliorate patients involved with oral health conditions or dental procedures?”.…”
Section: Introductionmentioning
confidence: 99%